Hot-electron dynamics mediated medical diagnosis and therapy - Luo, Bing (2024)
Surface plasmon resonance excitation significantly enhances the absorption of light and increases the generation of “hot” electrons, i.e., conducting electrons that are raised from their steady states to excited states. These excited electrons rapidly decay and equilibrate via radiative and nonradiative damping over several hundred femtoseconds. During the hot-electron dynamics, from their generation to the ultimate nonradiative decay, the electromagnetic field enhancement, hot electron density increase, and local heating effect are sequentially induced. Over the past decade, these physical phenomena have attracted considerable attention in the biomedical field, e.g., the rapid and accurate identification of biomolecules, precise synthesis and release of drugs, and elimination of tumors. This review highlights the recent developments in the application of hot-electron dynamics in medical diagnosis and therapy, particularly fully integrated device techniques with good application prospects. In addition, we discuss the latest experimental and theoretical studies of underlying mechanisms. From a practical standpoint, the pioneering modeling analyses and quantitative measurements in the extreme near field are summarized to illustrate the quantification of hot-electron dynamics. Finally, the prospects and remaining challenges associated with biomedical engineering based on hot-electron dynamics are presented.